The Dual System of Privacy Rights in the United States. - McThomas, Mary (Law, courts and politics., 2013)
Theoretically, the right to privacy is an individual's right to space away from the public gaze to make life choices that are best for her or him, regardless of the beliefs of the majority. Yet the right to privacy in the United States has proven problematic for both political theorists and constitutional scholars, as it does not conform to theoretical conceptions of privacy or to existing theories of constitutional development. Mary McThomas provides a new model that helps us to think about both the right to privacy as well as constitutional development. She first divides priv.